Silver nanoparticles: A review of the production techniques to reduce toxicological risk in ecosystems and in human health - Erica T. dos Santos Lima; Victoria L. Santana dos Santos; Camilla A. S. Valença; Sona Jain; Juliana C. Cardoso; Ricardo L. C. de Albuquerque-Júnior; André M. Lopes; Karolline Krambeck; Patricia Severino; Eliana B. Souto (German Journal of Pharmaceuticals and Biomaterials, 2024)
Silver nanoparticles (AgNPs) are being proposed as a new pharmaceutical product because of their antimicrobial properties and eco-toxicological profile. AgNPs can be synthesized by physical or chemical methods. However, green synthesis, the so-called biosynthesis in which organic or biological materials are used, is becoming even more popular as it is economically sustainable and non-toxic. The latter plays a significant role in loading important bioactives during the synthesis. This review discusses the state of the art of using AgNPs as antimicrobial agents and their green synthesis and environmental impact. It focuses on works published since 2019 using new molecules, e.g., plant extracts, acids, bacteria and fungi, as innovative pharmaceuticals against antimicrobial resistance. A bibliometric map of works published since 2022 indexed to the Scopus core collection is also discussed, highlighting the main research areas of this innovative topic. Their physicochemical properties strongly influence the use of AgNPs and impact ecosystems and  human health. Several approaches are described for their synthesis, highlighting that the toxicological risk can be mitigated by adopting green-based methodologies.